Nonclinical safety evaluation of food colorant lac dye via systematic toxicity profiling with assessment of in vivo antigenic potential - Park, Jin-Sung; Kim, Seung-Hyun; Kim, Yun-Soon; Kwon, Euna; Lim, Hyun-Jin; Han, Kang-Min; Choi, Yang-Kyu; Jung, Chul-Woo; Kang, Byeong-Cheol (Frontiers in Pharmacology, 2022)
Lac dye is a natural colorant derived mainly from the insect Kerria lacca (Kerr) and has been used in food and beverage as a red-coloring additive. Despite its increasing use for human consumption as an alternative for allergy-associated cochineal, toxicity profile remained incomplete to sufficiently assess its safety for the intended use. In this study, we evaluated systemic and genetic toxicity by performing acute and sub-acute oral toxicity studies in Sprague-Dawley (SD) rats using highly-purified lac dye (LD) formulated in water and a battery of genotoxicity tests, respectively. To further assess antigenic potentials, we carried out an in vivo passive cutaneous anaphylaxis test. Single dose of LD did not cause mortality at 5000 mg/kg body-weight (BW), setting oral LD50 of > 5000 mg/kg BW in SD rats. In the 90-day study, transient salivation without accompanying histopathological lesions in the salivary glands of 200 and 500 mg/kg BW groups and red-purple pigmentation on the surface of femora and skulls in 500 mg/kg groups were observed as non-adverse effects in associated with LD, and no adverse effect was detected in all the parameters examined, establishing 500 mg/kg BW as no-observed-adverse-effect-level (NOAEL). Furthermore, LD was not mutagenic nor clastogenic in the genotoxicity tests. When tested for antigenicity, LD did not induce anaphylactic skin responses as opposed to the positive reaction by ovalbumin, suggesting lack of antigenicity. Taken together, these findings provide extended toxicity information on LD with direct evidence supporting lack of antigenicity, providing an essential guidance for its safe use in human.